Hidden Curriculum and the Formation of Santri Obedience Character: A Phenomenological Study at Pondok Pesantren Annuqayah - Amirul Muttaqin; Moh. Ali; Siti Yumnah; Iri Hamzah; Agus Joko Purwanto (Kopertais Wilayah X Jawa Tengah, 2026)
This study is grounded in the urgency of strengthening character education within Islamic boarding schools, particularly through the mechanism of the hidden curriculum that operates implicitly in students’ daily lives. Although studies on pesantren education have developed significantly, limited attention has been given to micro-cultural practices as a medium for internalizing obedience values. This study aims to examine the hidden curriculum in shaping students’ obedience character and to identify its empirical manifestations through symbolic practices at Annuqayah Islamic Boarding School. A qualitative approach with a phenomenological design was employed. Data were collected through in-depth interviews, participant observation, and documentation involving 10-15 informants, including a kiai, administrators, senior students, junior students, and alumni. Data analysis was conducted through data reduction, open coding, categorization, and thematic analysis. The findings indicate that the hidden curriculum is manifested in five main themes: symbolic meaning, mechanisms of value transmission, the process of internalizing obedience, impacts on students’ behavior, and variations in interpretation. The practice of arranging the kiai’s sandals embodies the values of mahabbah (affection), tawadhu’ (humility), and barokah (blessing), which are internalized through modeling, habituation, and informal social interaction. Students’ obedience develops progressively from practical actions to reflective and spiritual awareness, contributing to improved social ethics and responsibility. This study affirms that the hidden curriculum functions as a cultural mechanism operating through lived experience and everyday practices in shaping students’ obedience character, while contributing to the development of contextual and sustainable character education based on local wisdom.